HUBUNGAN SMARTPHONE DENGAN KUALITAS TIDUR REMAJA DI SMA NEGERI 2 MAJENE - irfan, irfan; Aswar, Aswar; Erviana, Erviana (Universitas Islam Negeri Alauddin Makassar, 2020)
Gadgets are a technological tool that is currently developing rapidly. Technological developments require teenagers to use gadgets every day. The high use of gadgets at night will lead to insufficient healthy sleep needs in adolescents so that the quality and time of sleep is reduced. The purpose of this study was to determine whether there is a relationship between gadget use and adolescent sleep quality. This type of research is quantitative with a Cross Sectional Study approach with the Non Random Sampling method and the questionnaire used in the use of gadgets is the Smartphone Compulsion Test while the sleep quality questionnaire is the KKT. The sample used was 100 students. The results of the analysis that has been tested by Chi Square show that the hypothesis tested in the study is accepted with a significant value of 0.000, which means less than 0.05 (p> 0.05). It can be concluded that there is a significant relationship between the use of gadgets and the sleep quality of adolescents in SMA Negeri 2 Majene. It is hoped that teenagers can limit their use of gadgets and use gadgets properly without disturbing sleep quality. Keywords: Gadgets, Sleep Quality, Teenagers